Mobile Application Development on Infaq Finder (M-DoIF) using MADLC / Nur Miftah Farihah Azman - Azman, Nur Miftah Farihah (2015)
Technology development is growing faster and attracting attention in the eye of people. Mobile Application Development on Infaq Finder (M-DoIF) is one application project designed to make it easier for users to find the places for donate. The problem occurs when the residents do not know the place to donate the basic necessities and a lot of excess goods provided by the public occur at welfare homes. The objective of this project is to identify and analyze the user requirements, to design and to develop a prototype for Application Development on Infaq Finder (MDoIF). Mobile Application Development Lifecycle (MADLC) methodology has been used to achieve the objectives of this project and to get perfect results throughout the development process. In the questionnaire that have been distributed around Shah Alam and nearest place area to know the respond from user if the mobile application will help or not in the process of donating. The result indicated mostly respondent agreed and support this application should be develop because it easier for user to find right places to donate and help needy people. As for recommendations, M-DoIF should do a joint venture with any NGOs or Government sector to get the data and information about the welfare home and those people really need. M-DoIF can give benefit for user and to easier them to donate.